The Antecedents and Consequences of Customer Satisfaction for Firms - Anderson, Eugene W.; Sullivan, Mary W. (Marketing Science, 1993)
This research investigates the antecedents and consequences of customer satisfaction. We develop a model to link explicitly the antecedents and consequences of satisfaction in a utility-oriented framework. We estimate and test the model against alternative hypotheses from the satisfaction literature. In the process, a unique database is analyzed: a nationally representative survey of 22,300 customers of a variety of major products and services in Sweden in 1989–1990. Several well-known experimental findings of satisfaction research are tested in a field setting of national scope. For example, we find that satisfaction is best specified as a function of perceived quality and “disconfirmation”—the extent to which perceived quality fails to match prepurchase expectations. Surprisingly, expectations do not directly affect satisfaction, as is often suggested in the satisfaction literature. In addition, we find quality which falls short of expectations has a greater impact on satisfaction and repurchase intentions than quality which exceeds expectations. Moreover, we find that disconfirmation is more likely to occur when quality is easy to evaluate. Finally, in terms of systematic variation across firms, we find the elasticity of repurchase intentions with respect to satisfaction to be lower for firms that provide high satisfaction. This implies a long-run reputation effect insulating firms which consistently provide high satisfaction.